HUBUNGAN TINGKAT STRES TERHADAP GANGGUAN POLA TIDUR PADA MAHASISWA SKRIPSI PRODI KEPERAWATAN DI STIKES YATSI TANGERANG - Eka Noviana Nasriyanto; Refy Melinda; Rina Puspita Sari (Nusantara Hasana Berdikari, 2022)
Stress is a non-specific response of the body to any demands or workload. Students often face obstacles, obstacles in doing thesis so that students are vulnerable to stress and disturbed sleep patterns when completing the thesis. The purpose of this study was to determine the relationship between stress levels and sleep pattern disturbances in nursing undergraduate thesis students at STIKes Yatsi Tangerang. This study used an analytical sampling research design (total sampling). The population in this study were active students at level 4B and 4C totaling 101 students at STIKes Yatsi Tangerang. The research instrument used the DASS (Depression Anxiety Stress Scale) questionnaire to measure stress levels in students consisting of 20 questions and the PSQI (Pittsburgh Sleep Quality Index) questionnaire to measure sleep pattern disturbances consisting of 6 questions. Data analysis using univariate and bivariate using chi square. And the results of the chi square analysis obtained P value = 0.00 (P <0.05) which means that it can be concluded that there is a relationship between stress levels and sleep pattern disorders in nursing undergraduate thesis students at STIKes Yatsi Tangerang.